유네스코 기후변화 윤리원칙 선언: 함의와 쟁점 - 이상욱 (인간연구, 2019)
이 논문은 2017년 공표된 유네스코 기후변화 윤리원칙 선언의 제정 과정과 그 내용의 윤리적, 실천적 쟁점을 분석하고 이 선언이 기후변화에 대한 지구적 수준의 대응에 대해 갖는 시사점을 논의한다. 유네스코 기후변화 윤리원칙 선언은 전문가 집단이 마련한 초안이 각 회원국의 이해관계를 반영하는 과정에서 규범적 성격이 많이 약화되긴 했지만, 그럼에도 불구하고 기후변화라는 인류가 직면한 파국적 위기에 대해 추상적인 윤리 원칙만이 아니라 그 원칙이 효과적으로 실현되기 위한 정책적 대응을 회원국에게 주문했다는 점에서 큰 의의를 가진다. 이런 점을 고려할 때 유네스코 기후변화 윤리원칙 선언은 이론철학적 규범 논의가 나라마다 다른 사회문화적 배경에서 어떻게 구현되는 것이 바람직한지에 대한 실천윤리적 탐색에 좋은 사례를 제공한다. In this paper, I discuss the historical developments and the ethical and practical concerns relating to UNESCO′s 2017 Declaration of Ethical Principles in Relation to Climate Change. I also examine the implications of the Declaration in terms of the global response to climate change. The normative force of the Declaration′s original form, as prepared by a group of experts, has been notably weakened as a result of the inter-governmental consultation process. Nevertheless, the Declaration is significant in that it requires the member states to implement concrete policies consistent with the ethical principles, so that measures taken to address climate change should be effective. In this respect, the Declaration may be regarded as a prime example of how theoretical, and philosophical discussions of normativity can be implemented differently, depending on local socio-cultural contexts.
Keywords: 유네스코; 기후변화; 윤리원칙 선언; 실천윤리; 규범성; UNESCO; climate change; ethical principles Declaration; practical ethics; normativity